2020
DOI: 10.3389/fnins.2020.00284
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Transcutaneous Vagus Nerve Stimulation: Challenges for Translation to Clinical Practice

Abstract: Several studies have illustrated that transcutaneous vagus nerve stimulation (tVNS) can elicit therapeutic effects that are similar to those produced by its invasive counterpart, vagus nerve stimulation (VNS). VNS is an FDA-approved therapy for the treatment of both depression and epilepsy, but it is limited to the management of more severe, intervention-resistant cases as a second or third-line treatment option due to perioperative risks involved with device implantation. In contrast, tVNS is a non-invasive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
199
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(245 citation statements)
references
References 127 publications
1
199
0
6
Order By: Relevance
“…Despite its extensive use (Yap et al, 2020) and advantages, the lower sensitivity at the earlobe requires higher currents to produce a comparable subjective intensity. Future studies could apply additional control conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its extensive use (Yap et al, 2020) and advantages, the lower sensitivity at the earlobe requires higher currents to produce a comparable subjective intensity. Future studies could apply additional control conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation intensity, often determined by the patients themselves based on discomfort threshold, may be reported as amplitude (mA) and/or voltage (V). Reports go up to 60 mA or 24 V, but the final intensity setting is often not reported (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, citations of all selected studies were hand searched to identify additional studies. The citations of relevant reviews (Murray et al, 2016;Yap et al, 2020) were also searched to identify aVNS clinical RCTs. Through these citation searches, 5 additional studies were found.…”
Section: Search Methodsmentioning
confidence: 99%